2010
DOI: 10.1097/qad.0b013e3283398da1
|View full text |Cite
|
Sign up to set email alerts
|

Low rate of seroconversion after vaccination with a split virion, adjuvanted pandemic H1N1 influenza vaccine in HIV-1-infected patients

Abstract: Seroconversion after one dose of a split virion, inactivated, adjuvanted pandemic H1N1 influenza vaccine of HIV-infected patients was 69%. Studies to investigate whether a second dose of the vaccine will increase seroconversion rate are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
7
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 19 publications
4
39
7
1
Order By: Relevance
“…One prospective, observational study found seroconversion (defined as HIA titers ≥40 or ≥4 fold higher after vaccination) in 69% of 160 HIV-infected persons (mean CD4 cell count 523 cells/μL, 90% receiving HAART) after one dose of AS03-adjuvanted influenza A/California/7/2009 (H1N1) vaccine, which was lower than the 79%-98% seroconversion rate reported for the general population [86]. In this study, seroconversion was associated with younger age and higher CD4 cell count.…”
Section: Postexposure Chemoprophylaxis and Ph1n1 Vaccine Among Hiv-inmentioning
confidence: 76%
“…One prospective, observational study found seroconversion (defined as HIA titers ≥40 or ≥4 fold higher after vaccination) in 69% of 160 HIV-infected persons (mean CD4 cell count 523 cells/μL, 90% receiving HAART) after one dose of AS03-adjuvanted influenza A/California/7/2009 (H1N1) vaccine, which was lower than the 79%-98% seroconversion rate reported for the general population [86]. In this study, seroconversion was associated with younger age and higher CD4 cell count.…”
Section: Postexposure Chemoprophylaxis and Ph1n1 Vaccine Among Hiv-inmentioning
confidence: 76%
“…22,23 In contrast, other work has suggested a lower response in HIV-infected individuals, even in successfully treated patients. [18][19][20] It may be speculated that the apparent discrepancy is mainly attributable to the baseline level of reactivity to influenza virus antigen that is clearly higher in the HIV group.…”
Section: Discussionmentioning
confidence: 99%
“…17 In pandemic A/H1N1 influenza vaccine studies, the data are contrasting. In fact, several studies on the efficacy of MF59-adjuvanted 2009 pandemic A/H1N1 influenza vaccine (A/H1N1/Cal/09) suggested a lower rate of influenza seroconversion in HIV-infected individuals (36.4-69%) as compared with healthy donors ( > 79%), [18][19][20] even in patients with high CD4 T cell counts. 21 In contrast, other studies reported a good antibody response in successfully HAART-treated HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Für Personen, die noch keinen Kontakt zu Influenzaviren oder -Antigenen hatten und bei denen keine ausreichende Grundimmunität mehr vorausgesetzt werden kann, werden eventuell zwei Impfungen notwendig sein, oder es sind Impfstoffe mit Adjuvanzien vorzuziehen. Wirkstoffverstärkte Grippeimpfstoffe sind gerade für Menschen ab 65 Jahre oder immunsupprimierte Patienten indiziert [4,13].…”
unclassified